Rubber composition for inner liner of pneumatic vehicle tire

By using materials such as halogenated butyl rubber, chloride butyl rubber and HTT lignin in the pneumatic tire lining rubber composition, combined with zinc oxide and sulfur vulcanization systems, the airtightness and crack resistance of the lining are solved. , achieving weight reduction and environmentally friendly performance improvements.

CN119255920APending Publication Date: 2025-01-03SUNCOAL INDS GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380028641.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2023-03-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to provide rubber compositions suitable for pneumatic tire linings, especially in poor performance in terms of airtightness and crack resistance, with weight gain and environmentally friendly problems.

Method used

Rubber compositions containing halogenated butyl rubber and chloride butyl rubber are used, and biomass-based fillers with specific 14C content, carbon content and surface acidic hydroxyl groups, such as HTT lignin as a replacement carbon black, combined with zinc oxide and sulfur vulcanization system to prepare a large number of filler rubber compositions with improved airtightness and crack resistance.

Benefits of technology

It achieves a reduction in gas permeability, reduces crack propagation and weight, while improving the airtightness and crack resistance of the rubber composition, meeting the multiple performance requirements of pneumatic tire linings, and using environmentally friendly biomass materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049561650000311
    Figure BDA0005049561650000311
  • Figure BDA0005049561650000321
    Figure BDA0005049561650000321
  • Figure BDA0005049561650000341
    Figure BDA0005049561650000341
Patent Text Reader

Abstract

The present invention relates to a rubber composition comprising a rubber component comprising at least one halogenated butyl rubber in an amount of from 60 phr to 100 phr and a filler component comprising a filler F1 having a 14C content in the range of from 0.20 Bq / g carbon to 0.45 Bq / g carbon, a carbon content in the range of from 60% by weight to 85% by weight and having acidic hydroxyl groups on the surface; wherein the weighted arithmetic mean of the STSA surface area of the filler F1 is in the range of 40 m2 / g to 80 m2 / g; the filler F1 has a volume-based median particle size distribution Dv (50) in the range of 0.5 [mu] m to 5 [mu] m and a volume-based Dv (97) value in the range of 3 [mu] m to 23 [mu] m; and (i) the filler component comprises more than 45 phr of a filler F1; or (ii) the filler component comprises more than 25 phr of a filler F1 and additionally comprises one or more industrial carbon black F2 wherein the weighted arithmetic mean of the STSA surface area of the industrial carbon black F2 is in the range of 55 m2 / g to 95 m2 / g. The invention also relates to vulcanizable and vulcanizable rubber compositions based on the aforementioned rubber composition, to a kit for preparing a vulcanizable rubber composition, and to a method for preparing a rubber composition and vulcanizable rubber composition. In addition, the present invention relates to a method of further processing a vulcanizable rubber composition. The invention also relates to application of the lignin subjected to hydro-thermal treatment in preparation of a rubber composition for a lining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to rubber compositions, more particularly to vulcanizable and vulcanized rubber compositions for innerliners of pneumatic vehicle tires. The present invention also relates to kits of parts for their manufacture and methods for their manufacture and further processing, as well as methods for the manufacture of pneumatic tires. The present invention also relates to the use of special fillers made from recycled raw materials for the preparation of rubber compositions, in particular rubber compositions for innerliners. Background Art

[0002] Pneumatic vehicle tires have a complex construction. The requirements placed on them vary accordingly. On the one hand, short braking distances must be ensured on dry and wet roads, and on the other hand, they must have good wear resistance and low rolling resistance. In addition, vehicle tires must meet the requirements of the legislator.

[0003] To ensure this diverse performance, the individual tire components are specialized and consist of a variety of different materials such as metal, polymer textile materials and various rubber-based components.

[0004] According to the design of pneumatic tires, a distinction is made between radial tires, cross-ply tires and bias-ply tires or bias-belted tires. Taking a typical pneumatic tire as an example, a radial-ply tire comprises at least a belt, a belt cover, a tread, a reinforcing strip, a sidewall, a bead filler, a bead wire, an inner liner and a carcass.

[0005] The belt usually consists of multiple layers of twisted steel wires, which are coated with rubber and arranged at an angle. Its main purpose is to provide structural strength to the tire in its inflated state. The belt further provides driving stability during acceleration, braking and cornering. It affects rolling resistance and significantly benefits the tire's mileage.

[0006] The annular belt cover between the tread and the upper annular belt is used to improve high-speed performance and limit the tire diameter as speed increases.

[0007] The tread itself plays an important role in the driving characteristics. The rubber compound of the tread determines the wear characteristics and the dynamic driving characteristics in different weather conditions (on wet and dry roads, in cold and warm weather, on ice and snow). In turn, the design of the tread pattern largely determines the behavior of the tire in aquaplaning and wet conditions and on snow, and also determines its noise behavior.

[0008] Reinforcing strips may optionally be used in the bead filler area to further improve the strength and handling characteristics of the tire.

[0009] The sidewall protects the carcass from lateral damage and atmospheric influences. The rubber compound used for the sidewall is flexible and wear-resistant, containing a relatively large amount of aggregate to protect against aging and ozone.

[0010] The bead filler is located on the bead wire / bead core. Its shape and configuration provide driving stability and have an influence on steering precision and suspension comfort. The rubber compounds used for bead fillers are usually very strong and relatively stiff, which is ensured in particular by the high degree of crosslinking using a high-dose vulcanization system and the choice of filler.

[0011] The bead wire is the inner part of the tire bead and consists of twisted steel wires coated with rubber, which are coiled in a ring shape and firmly fix the tire on the rim. In the common tubeless configuration, the tire bead (also called tire base or foot) is pressed against the rim flange to close the tire in an airtight manner. The steel cords and wires in the bead core of an all-steel tire, the steel cords and wires in the tread or carcass must be firmly connected to the surrounding rubber compound to play the role of composite material. To this end, the steel wires are usually coated with brass or bronze. Only afterwards are they formed into tire forming parts using the wire bonding compound, which is then assembled into the tire blank. Due to its high proportion of natural rubber, the wire bonding compound is relatively strong, crack-resistant, and a strong connection with the brass or bronze coating is achieved, for example, by special resin additives and a high sulfur content. A permanent connection is formed during the vulcanization process.

[0012] The carcass forms the basic structure of the tire and consists of one or more layers of textile fabric (rayon, nylon, polyester, aramid) or steel cord layers (for trucks) embedded in rubber. The carcass is held under tension by the tire air pressure and is therefore essentially responsible for the force transmission between the rim and the tread / street. It is connected to the tire bead at the base of the tire, thus holding the tire together. The carcass, as a composite material, plays a role between the cord layers that ensure strength and force transmission and the rubber compound that wraps the parallel cords. Due to the constant deformation of the tire, the cord compound must be fatigue-resistant, which is usually achieved through a blend of natural and synthetic rubber, but it must also form a strong connection with the cords. To achieve this, the cords are coated with a rubber compound after stranding / twisting. Cords with this treatment are coated with an uncured rubber compound. The resin system in the special compound then reacts with the cord finish during the vulcanization process to form a durable composite material.

[0013] As mentioned above, modern tires are usually tubeless. The so-called inner liner is a layer of rubber compound that is arranged radially inwards and is impermeable to air to the greatest extent possible. It is also called the inner core or inner plate and serves to ensure that the air pumped into the tire cannot escape over a long period of time, as the air pressure significantly affects the driving characteristics and durability of the tire. In addition, the internal pressure also has an effect on the rolling resistance of the tire. A reduction in air pressure leads to higher dynamic deformations of the tire, which in turn leads to the unnecessary conversion of part of the kinetic energy into heat energy. This has a negative impact on the vehicle's fuel consumption and thus on the associated CO2 emissions.

[0014] In addition, the inner liner protects the carcass from diffusion of air and moisture therein and prevents any damage to the strength-providing elements of the carcass and / or the annulus. In order to keep the inner liner as airtight as possible, it should also have good crack resistance and fatigue resistance so that cracks that affect airtightness will not occur during driving.

[0015] Due to this specific requirement, rubber compounds for innerliners have a completely different composition than rubber compounds for other tire components, both in terms of the rubbers and fillers used and the weight proportions of the components relative to each other, but they still need to be compatible with the adjacent tire components and, in particular, need to have good adhesion to these components. In addition to the type of rubber, the minimum amount of the different rubbers in the rubber compound also plays an important role, as do the various specific parameters and properties of the fillers that can be used.

[0016] Among them, halogenated butyl rubber, such as chlorobutyl rubber or bromobutyl rubber, is occasionally blended with other rubbers and used as lining rubber. Butyl rubber and halogenated butyl rubber have low gas permeability. Halogenated butyl rubber is blended with other rubbers (such as natural rubber) to increase viscosity, reduce costs and adjust mechanical properties during assembly.

[0017] The gas tightness of the inner liner can be further increased by additionally dosing low-activity or inactive bulky fillers into the rubber compound of the inner liner. The fillers used to date include, in particular, furnace black.

[0018] In order to prevent crack formation under dynamic loads, the liner must have a balanced elastic modulus and matching hardness, which usually conflicts with a high proportion of inactive fillers. Therefore, mineral oil-based softeners are often added to rubber compositions, which reduces the elastic modulus and hardness of the composition, but at the same time increases the gas permeability, resulting in a relatively narrow optimal range for the use of mineral oil-based softeners and fillers.

[0019] In addition, many fillers, such as N 660 carbon black, have a density of about 1.8 g / cm 3The relatively high density of the filler is higher than that of the tyre. Therefore, the rubber composition compounded with such fillers also has a higher density and therefore a higher weight for the same volume. However, the higher the density of the filler, the heavier the weight of the innerliner and ultimately the weight of the pneumatic tire, which in turn leads to higher fuel consumption. In particular, carbon blacks of the types N 660 and N 772 are used in the production of innerliners.

[0020] Industrial carbon black is usually produced by petrochemicals, through incomplete combustion or pyrolysis of hydrocarbons. However, from an environmental point of view, the use of fossil energy to produce fillers must be avoided or minimized. Instead, the goal should be to provide composite fillers based on biomass that meet the multiple requirements of liner.

[0021] In the field of preparing rubber compositions generally for tires, WO 2017 / 085278 A1 discloses, inter alia, the use of so-called HTT lignin (lignin converted by hydrothermal treatment) as a filler to replace industrial carbon black.

[0022] Lignins are solid biopolymers that are incorporated into plant cell walls, thus affecting the lignification of plant cells. Therefore, their inclusion in biorenewable raw materials - especially in hydrothermally treated form - has the potential to become an environmentally friendly alternative to industrial carbon black in rubber compositions.

[0023] WO 2017 / 194346 A1 describes the use of HTT lignin in rubber compounds for pneumatic tire components, in particular in combination with methylene donor compounds such as hexa(methoxymethyl)melamine to increase the stiffness of cured rubber components of pneumatic tires, and, in particular, substituted phenolic resins, and / or in combination with silane coupling agents. One of the goals of the treatment in WO 2017 / 194346 is to reduce the rolling resistance of the tire. Natural rubber, polybutadiene rubber, styrene-butadiene rubber and polyisoprene rubber are referred to as suitable rubber materials. WO 2017 / 194346A1 discloses the suitability of the rubber compound described therein for the tread area, sidewalls and beads of pneumatic tires. Rubber compounds that meet the requirements for innerliners are not described in this document.

[0024] EP 3 470 457 A1 also discloses a vulcanizable sulfur-containing rubber compound for vehicle tires. The filler used for the solvent-polymerized styrene-butadiene rubber (SSBR) tested was HTT coal, which is obtained from various raw materials, produced by adding metal halides, and exhibits a BET surface area of ​​up to more than 180 m 2 / g. Among them, the BET surface area was found to be 90m 2 / g to 140m 2 HTT coals having an average surface roughness of 0.1 wt % and an average surface functionality of 0.1 wt % are particularly preferred as they are said to exhibit enhanced surface roughness and optimized surface functionality.

[0025] WO 2020 / 202125 A1 teaches for the first time the use of halogenated butyl rubber in combination with up to 45 phr (parts per hundred parts by weight of rubber) of HTT lignin in the field of inner liner production, although in the examples of WO 2020 / 202125 A1 it is never used as the sole filler, but only in combination with N 660 type carbon black. In particular, the above document teaches that the added carbon black must have a 30 m 2 / g to 50m 2 / g specific surface area, which is a characteristic of N 600 carbon black, and its BET surface area is 35m 2 / g (ASTM D 6556), STSA surface area is 34m 2 / g (ASTM D 6553). However, the HTT lignin content is limited to a maximum of 45 phr and the carbon black with a maximum specific surface area of ​​50 m 2 The limitation of a mixture of 100 Å / g of carbon black both proved to be a surprisingly disadvantageous factor in reducing gas permeability and maintaining low crack growth, even though the latter carbon black is the carbon black commonly used for innerliners.

[0026] Therefore, from the overview of the prior art, there is a particular need for a rubber composition or rubber compound suitable for pneumatic tire innerliners, which contains an environmentally friendly material based on recycled raw materials to replace carbon black as a filler, and provides a vulcanized rubber composition that meets the requirements of pneumatic tire innerliners, especially in terms of air tightness and crack resistance, and has improved tear propagation resistance. Summary of the invention

[0027] The problem underlying the present invention can be solved by providing a rubber composition comprising

[0028] Rubber component,

[0029] comprising at least one halogenated butyl rubber selected from the group consisting of brominated butyl rubber and chlorinated butyl rubber, and

[0030] Filler ingredients,

[0031] Contains one or more fillers F1, the filler F1 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon;

[0032] The carbon content is in the range of 60% to 85% by weight relative to the ash-free and water-free filler;

[0033] having acidic hydroxyl groups on its surface; wherein

[0034] The weighted arithmetic mean of the STSA surface area of ​​filler F1 is 40m 2 / g to 80m 2 / g range;

[0035] Volume-based median particle size distribution D of filler F1 v (50) In the range of 0.5 μm to 5 μm, the volume-based D v (97) values ​​range from 3 μm to 23 μm;

[0036] and

[0037] i. the filler composition contains more than 45 phr of filler F1; or

[0038] ii. The filler component contains more than 25 phr of filler F1 and further contains one or more industrial carbon blacks F2, wherein the weighted arithmetic mean of the STSA surface area of ​​the industrial carbon blacks F2 is within 55 m 2 / g to 95m 2 / g range;

[0039] The amount of the halogenated butyl rubber in the rubber composition is 60 phr to 100 phr.

[0040] The phr (parts by weight per hundred parts of rubber) specification used herein is a quantitative specification for compound formulations commonly used in the rubber industry. The dosage of parts by weight of each component is always based on 100 parts by weight of the total mass of all rubbers present in the compound.

[0041] Hereinafter, this rubber composition will also be referred to as a rubber composition according to the invention or a rubber composition according to the present invention.

[0042] The invention also relates to a vulcanizable rubber composition comprising or consisting of the rubber composition according to the invention and a vulcanization system containing zinc oxide and / or sulfur.

[0043] Hereinafter, such a vulcanizable rubber composition will also be referred to as a vulcanizable rubber composition according to the invention or a vulcanizable rubber composition according to the present invention.

[0044] Another object of the invention is a kit of parts which comprises, in spatially separated form, a rubber composition according to the invention and a vulcanization system containing zinc oxide and / or sulfur.

[0045] In the following, this kit of parts will also be referred to as kit of parts according to the invention or kit of parts according to the invention.

[0046] Another object of the present invention is a method for preparing a rubber composition according to the invention and a vulcanizable rubber composition according to the invention, the latter being obtained by compounding the components of the rubber composition in a first stage to prepare the rubber composition according to the invention as a base compound (masterbatch) and mixing the components of the vulcanization system in a second stage.

[0047] These methods will also be referred to as methods according to the invention for preparing the rubber composition according to the invention or the vulcanizable rubber composition according to the invention.

[0048] Another object of the present invention is a method for further processing the vulcanizable rubber compositions according to the invention, in which they are formed into a web by calendering, extrusion or the so-called roll head process.

[0049] This method will also be referred to as method for further processing according to the invention or method for further processing according to the invention.

[0050] Another object of the invention is a method for manufacturing a pneumatic tire, comprising the method of further processing according to the invention, followed by a step of cutting the obtained web to the size of a pneumatic tire innerliner, and comprising a subsequent step of vulcanizing the innerliner thus obtained, preferably together with the pneumatic tire carcass.

[0051] This method will also be referred to as a method for manufacturing a pneumatic tire according to the invention or a method for manufacturing a pneumatic tire according to the present invention.

[0052] Another object of the invention is the use of a filler F1 suitable for the context of the invention and as characterized above, and of a filler mixture comprising F1 and F2, in a rubber composition for an inner liner, wherein fillers F1 and F2 are used in a total amount of at least 46 phr.

[0053] This use will also be referred to as use according to the invention or use according to the invention. DETAILED DESCRIPTION

[0054] Hereinafter, each component of the rubber composition respectively used in the above-mentioned rubber composition, method and use, and a particularly suitable process sequence will be described in detail.

[0055] Rubber composition

[0056] rubber

[0057] In the context of the present invention, one or more halogenated butyl rubbers selected from the group consisting of chlorinated butyl rubber (CIIR; chloroisobutylene-isoprene rubber) and brominated butyl rubber (BIIR; brominatedisobutylene-isoprene rubber) are used.

[0058] Halogenated butyl rubbers are halogenated isobutylene-isoprene rubbers. They can be obtained by halogenating, in particular brominating and / or chlorinating butyl rubbers.

[0059] In turn, butyl rubber consists mainly of isobutylene units, the remainder being isoprene units. It is particularly preferred that the proportion of isobutylene units is 95 mol % to 99.5 mol %, the proportion of isoprene units is 0.5 mol % to 5 mol %, and it is more particularly preferred that the proportion of isobutylene units is 97 mol % to 99.2 mol % and the proportion of isoprene units is 0.8 mol % to 3 mol %, wherein the proportion of isobutylene units and isoprene units preferably add up to 100 mol % of the monomers contained in the polymer and polymerized therein. Butyl rubber generally has a low gas permeability and water permeability.

[0060] Due to the isoprene units polymerized therein, butyl rubber has carbon-carbon double bonds which are available both for vulcanization and for modification with halogens such as, in particular, chlorine and bromine.

[0061] Halogenated butyl rubbers, which can be obtained by modification with halogens (halogenation), have a higher reactivity than butyl rubber and therefore have a wider range of vulcanization possibilities, in particular co-vulcanization possibilities with other rubbers such as natural rubber (NR), butyl rubber (IIR; isobutylene-isoprene rubber) and styrene-butadiene rubber (SBR).

[0062] Among the halogenated butyl rubbers, bromobutyl is more reactive due to the weaker carbon-bromine bond compared to chlorobutyl, which has a carbon-chlorine bond, which opens up an even wider range of cure systems for bromobutyl. Bromobutyl cures faster and generally has better adhesion to diene rubbers.

[0063] Among the halogenated butyl rubbers, brominated butyl rubbers are particularly preferred in the context of the present invention.

[0064] However, it is also possible to use a composite of one or more brominated butyl rubbers and one or more chlorinated butyl rubbers as the halogenated butyl rubber component. Here, the brominated butyl rubber increases the vulcanization rate.

[0065] Chlorobutyl rubber (CIIR) suitable in the context of the present invention preferably contains 1.1 to 1.3% by weight of chlorine, and brominated butyl rubber (BIIR) preferably contains 1.9 to 2.1% by weight of bromine. This corresponds to a proportion of about 2 mol % of reactive sites.

[0066] The viscosity of the halogenated butyl rubber is preferably between 35 and 55 Mooney units (ML (1+8), 125° C.). Like butyl rubber, the product contains almost no secondary components (rubber ratio>98.5). The halogenated butyl rubber preferably contains a stabilizer, in particular a sterically hindered phenol as a stabilizer.

[0067] The rubber composition of the present invention may contain, in addition to the halogenated butyl rubber, one or more other rubbers than the halogenated butyl rubber.

[0068] As other rubbers other than halogenated butyl rubber, if present, natural rubber, butyl rubber and styrene-butadiene rubber are particularly preferred.

[0069] For example, therefore, by mixing natural rubber with halogenated butyl rubber, the adhesion to other rubber-based tire components can be increased, particularly compared to general-purpose rubber. By cross-linking different rubbers, synergy can be produced in terms of tensile strength, making it even higher than the tensile strength of a single rubber. Use a vulcanization system comprising zinc oxide, sulfur and thiazole, such as mercaptobenzothiazole disulfide (MBTS) is especially true. On the other hand, the gas permeability and moisture permeability of the vulcanized final product usually increase with the mixing of natural rubber.

[0070] The blending of styrene-butadiene rubber with halogenated butyl rubber can be carried out in the same manner as the blending of natural rubber, but generally has no particular advantages over the latter, and the use of natural rubber is therefore generally preferred to styrene-butadiene rubber in terms of the use of renewable resources. For example, typical natural rubber is available under the names SMR ("Standard Malaysian Rubber"), TSR ("Technical Graded Rubber") and RSS ("Smoked Sheet").

[0071] A mixture of up to 30 phr, preferably up to 20 phr, of butyl rubber with a halogenated butyl rubber generally has little or no effect on the gas and moisture permeability of the cured final product, but can, if desired, reduce the cure rate and increase heat resistance.

[0072] The total amount of halogenated butyl rubber is 60 to 100 phr, preferably 65 to 100 phr, particularly preferably 70 to 100 phr, further preferably 75 or 80 to 100 phr, more preferably 85 or 90 to 100 phr, such as 95 to 100 phr, most preferably 100 phr.

[0073] In the case where the rubber compound comprises less than 100 phr of halogenated butyl rubber, the rubber composition comprises at least one other rubber, preferably one of the abovementioned rubbers, more particularly preferably natural rubber, so that the total amount of rubber present is 100 phr.

[0074] This means that the amount of other rubbers than halogenated butyl rubber is 0 to 40 phr, preferably 0 to 35 phr, particularly preferably 0 to 30 phr, further preferably 0 to 20 phr or 25 phr, very particularly preferably 0 to 10 phr or 15 phr, for example 0 to 5 phr or 0 phr.

[0075] Filling F1

[0076] One or more fillers F1 must be used in the filler component.

[0077] Has 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon, preferably 0.23 Bq / g carbon to 0.42 Bq / g carbon;

[0078] having a carbon content in the range of 60% to 85% by weight, preferably 63% to 80% by weight, particularly preferably 65% ​​to 75% by weight, and very particularly preferably 68% to 73% by weight, relative to the ash-free, water-free filler;

[0079] The weighted arithmetic mean of the STSA surface area of ​​filler F1 is 40m 2 / g to 80m 2 / g, preferably 42m 2 / g to 75m 2 / g, more preferably 44m 2 / g to 70m 2 / g;

[0080] The volume-based median particle size distribution D of the filler or fillers F1 v (50) In the range of 0.5 μm to 5 μm, particularly preferably 1 μm to 4 μm, more particularly preferably 1 μm to 3 μm, based on volume D v (97) values ​​are in the range of 3 μm to 23 μm, preferably at most 15 μm, more particularly preferably at most 12 μm, even more preferably at most 10 μm, even more preferably at most 9 μm, even more preferably at most 8 μm, most preferably at most 7 μm, more particularly preferably at most 6 μm;

[0081] And one or more fillers F1 have hydroxyl groups on their surface.

[0082] The above required 14The C content is achieved by fillers F1 obtained from biomass by further processing or reaction, preferably by decomposition, wherein the decomposition can be carried out thermally, chemically and / or biologically, preferably thermally and chemically. Therefore, fillers obtained from fossil materials, such as, in particular, fossil fuels, do not fall within the definition according to the invention of fillers to be used according to the invention, since they do not have the corresponding 14 C content.

[0083] In the present context, biomass is in principle defined as any biomass, wherein the term "biomass" in the present context includes so-called phytomass, i.e. biomass derived from plants, animal matter, i.e. biomass derived from animals, and microbial biomass, i.e. biomass derived from microorganisms including fungi, wherein biomass is dry biomass or fresh biomass, derived from dead or living organisms.

[0084] The biomass particularly preferably used for preparing the filler F1 herein is plant matter, preferably dead plant matter. Dead plant matter includes in particular dead, rejected or detached plants and parts thereof. These include, for example, broken and torn leaves, lateral buds, branches and twigs, fallen leaves, felled or pruned trees, as well as seeds and fruits and their derived parts, and also sawdust, shavings / wood chips and other products derived from wood processing.

[0085] The above-mentioned carbon contents are usually achieved with fillers based on biomass decomposition and can be determined by elemental analysis in accordance with DIN 51732:2014-7.

[0086] Preferably, the oxygen content of filler F1 is in the range of 15% to 30% by weight, preferably 17% to 28% by weight, particularly preferably 20% to 25% by weight, relative to the ash-free and water-free filler. The oxygen content is defined herein as the difference from the carbon, hydrogen, nitrogen and sulfur contents.

[0087] In addition, the filler F1 of the above-defined type has acidic hydroxyl groups (so-called surface-available acidic hydroxyl groups) on its surface. According to Sipponen, the determination of surface-available acidic hydroxyl groups can be carried out qualitatively and quantitatively by colorimetry. Sipponen's method is based on the adsorption of basic dye Azure B to the available acidic hydroxyl groups on the filler surface. If there is corresponding adsorption under the conditions cited in item 2.9 (page 82) in the article described below, there are acidic surface-available hydroxyl groups in the sense of the present invention. More details can be obtained from the paper "Determination of surface-accessibleacidic hydroxyls and surface area of ​​lignin by cation dye adsorption" (Bioresource Technology169 (2014) 80-87). In the quantitative determination, the amount of surface-available acidic hydroxyl groups is given in mmol / g filler. Preferably, the amount of surface-available acidic hydroxyl groups is in the range of 0.05mmol / g to 40mmol / g, particularly preferably 0.1mmol / g to 30mmol / g, and more particularly preferably 0.15mmol / g to 30mmol / g. Preferred surface available acidic hydroxyl groups are phenolic hydroxyl groups.

[0088] There are also clear differences between biomass-based fillers in terms of their BET surface (specific total surface area according to Brunauer, Emmett and Teller) and their external surface (STSA surface area; statistical thickness surface area).

[0089] For example, WO 2017 / 085278 A1 describes hydrothermally treated lignin (i.e. fillers based on dead plant matter containing lignin obtained by hydrothermal treatment) with STSA surface areas of 5 m 2 / g to 200m 2 In the experimental part of the publication, it is even mentioned that the surface area of ​​STSA is only 2.6 m 2 / g those.

[0090] In the context of the present invention, particular mention is also made of the term weighted arithmetic mean of the STSA surface of the filler. The term "weighted arithmetic mean" is used in the context of the present invention in its usual meaning.

[0091] With regard to the STSA surface area relative to the filler F1, therefore, when only one filler F1 is used, the weighted arithmetic mean of the STSA surface area of ​​this filler corresponds exactly to the STSA surface area of ​​this filler F1, since its relative frequency is 1 (weighted arithmetic mean of the STSA surface area=[STSA surface area of ​​F1] x 1). When, for example, a mixture of two different fillers F1' and F1" is used, in which, for example, there are 70% by weight of filler F1' (corresponding to a relative frequency of 0.7) and 30% by weight of filler F1" (corresponding to a relative frequency of 0.3), the weighted arithmetic mean of the STSA surface area of ​​the filler F1=([STSA surface area of ​​F1'] x 0.7)+([STSA surface area of ​​F1"] x 0.3) or in general:

[0092] Weighted arithmetic mean of the STSA surface area of ​​filler F1 = ∑(STSA F1i xh i ), where STSA F1i Representative filler F1 i STSA surface area, h i Represents the relative amount of this filler.

[0093] Preferably, the STSA surface area of ​​each individual filler F1 is also 40 m 2 / g to 80m 2 / g, particularly preferably within the range of 40 m 2 / g to 75m 2 / g, more preferably in the range of 42m 2 / g to 70m 2 Of course, the selection of a single filler F1 is based on the mandatory requirement that the weighted arithmetic mean of the STSA surface area of ​​filler F1 is within 40 m 2 / g to 80m 2 / g, preferably 42m 2 / g to 75m 2 / g, particularly preferably 44m 2 / g to 70m 2 / g.

[0094] Volume-based median particle size distribution D of filler F1 v (50) is the minimum 0.5 μm and the maximum 5 μm, the volume-based particle size distribution value D v (97) is 3 μm at the minimum and 23 μm at the maximum. The volume-based particle size distribution median is in the range of 0.5 μm to 5 μm, particularly preferably in the range of 1 μm to 4 μm, and more particularly preferably in the range of 1 μm to 3 μm. The volume-based particle size distribution value D v(97) In the range of 3 μm to 23 μm, preferably up to a maximum of 18 μm, particularly preferably up to a maximum of 15 μm, more particularly preferably up to a maximum of 12 μm, even more preferably up to a maximum of 10 μm, even more preferably up to a maximum of 9 μm, even more preferably up to a maximum of 8 μm, most preferably up to a maximum of 7 μm, more particularly preferably up to a maximum of 6 μm. Particle size distribution and D v (50) or D v The (97) value was determined by laser diffraction as described in detail in the experimental section. v (97) is naturally always greater than D of the same filler F1 v (50) value.

[0095] The particle size distribution is not an intrinsic property of filler F1, but is directly derived from its production. In contrast, the biomass-based filler is depolymerized by a comminution process (e.g., grinding) to such an extent that the particle size distribution of the present invention is obtained. Too large a particle size of the filler particles will show lower reinforcement, which is reflected in a flat tensile strain curve, thereby reducing the tensile strength. Too small a particle size will make dispersion in the polymer matrix more difficult, and the filler particles will exist as insufficiently dispersed clusters.

[0096] exist 14 All of the above mentioned ranges characterizing the filler F1 with respect to C content, carbon and oxygen content, STSA surface area and surface available acid groups and particle size distribution apply equally to all fillers F1 used according to the invention, but preferably to lignin-based fillers, which represent herein a preferred class of fillers producible from plant matter.

[0097] In their textbook Kautschuk Technologie – Werkstoffe Verarbeitung Produkte (3rd revised and expanded edition 2013, pages 1196-1197), and Sommer divide various rubbers into three categories, namely, rubbers with low polarity and high oil swelling, rubbers with medium polarity and medium oil swelling, and rubbers with high polarity and low oil swelling. Although halogenated butyl rubber is reactive, its polarity is low.

[0098] It is therefore particularly surprising that the fillers F1 used according to the invention, in particular lignin-based fillers, have good compatibility with halogenated butyl rubbers which have only a low polarity, since the fillers used according to the invention have a high polarity compared to typical industrial carbon blacks, which is due in particular to the content of surface-available acidic hydroxyl groups. However, the higher oxygen content compared to industrial carbon blacks also contributes to this.

[0099] Among the lignin-based fillers F1, hydrothermally treated lignin-containing plant bodies are particularly preferred. The preferred treatment is a hydrothermal treatment in the presence of liquid water at a temperature of 150°C to 250°C. Compared with the original lignin, the carbon content is generally increased and the oxygen content is reduced. For example, a suitable treatment method is described in WO 2017 / 085278 A1. The lignin-based filler obtained by hydrothermal treatment will also be referred to as HTT lignin ("hydrothermally treated lignin") hereinafter. The term HTC lignin ("hydrothermally carbonized lignin") is also often used in the literature. Fillers referred to as HTC lignin also belong to the term HTT lignin. Hydrothermal treatment at a temperature of 150°C to 250°C in the presence of liquid water is also referred to as hydrothermal treatment hereinafter. The HTT lignin described below is a preferred filler F1 used in the context of the present invention.

[0100] In one embodiment, the rubber composition according to the invention comprises more than 45 phr, preferably at least 46 phr, particularly preferably from 48 to 80 phr, more particularly preferably from 50 to 75 phr and especially from 50 to 70 phr of the filler F1 defined above for use according to the invention.

[0101] In another embodiment, the rubber composition according to the invention comprises more than 35 phr, preferably at least 36 phr, particularly preferably 38 to 80 phr, more particularly preferably 40 to 70 phr, in particular 50 to 65 phr of a filler F1 used according to the invention as defined above in combination with one or more industrial carbon blacks F2, wherein the weighted arithmetic mean of the STSA surface area of ​​the industrial carbon blacks F2 is between 55 m 2 / g to 95m 2 In this embodiment, it is preferred that the sum of filler F1 and industrial carbon black F2 in the filler component is at least 40 phr, particularly preferably at least 43 phr to 80 phr, more particularly preferably 46 phr to 70 phr, especially 48 phr to 65 phr.

[0102] HTT Lignin

[0103] HTT lignin is obtained by hydrothermal treatment of lignin-containing raw materials and represents a particularly preferred filler F1 that can be used according to the invention. The properties of HTT lignin can vary within a wide range. For example, different HTT lignins differ in their BET and STSA surface areas, ash content, pH and heat loss, as well as density and particle size and the amount of surface available acidic hydroxyl groups and particle size distribution.

[0104] In the context of the present invention, as filler F1 used according to the invention, a special HTT lignin is used as a substitute material for the carbon black usually contained in the rubber composition for inner lining. For example, the preparation of HTT lignin that can be used according to the invention is described in WO 2017 / 085278 A1. The correspondingly produced filler F1 is crushed, in particular ground, until the desired particle size distribution is achieved.

[0105] Although the above-mentioned documents WO 2017 / 085278 A1 and WO 2017 / 194346 A1 generally mention the use of HTT lignin as a possible alternative material to carbon black in tires, it should not be concluded that the behavior of HTT lignin in ordinary rubber compositions is easily transferred to the special rubber composition of the present invention containing more reactive halogenated butyl rubber. This is especially true for their use in rubber compositions based on halogenated butyl rubber, because they have completely different properties from ordinary rubber compositions, and due to the high reactivity of halogen atoms, in particular chlorine atoms and especially bromine atoms, interactions and even reactions with fillers that can be used according to the present invention, in particular HTT lignin, must be expected, which have a chemically different surface and composition compared to industrial carbon black. In particular, the above-mentioned differences already mentioned in the presence of available acidic hydroxyl groups, preferably phenolic hydroxyl groups, on the surface of industrial carbon black and the fillers used in the present invention lead to surprisingly good incorporation of fillers and their compatibility with rubber components, even without the use of compatibilizers, especially when silane compounds are not used in the rubber composition of the present invention. The resulting vulcanizates have surprisingly good properties, wherein even critical properties, such as the very low gas permeability required for innerliners, are improved.

[0106] It is also surprising that, contrary to the teaching of WO 2020 / 0202125 A1, a larger amount of filler F1 with a STSA surface in the higher range can be used, in particular with a STSA surface area of ​​at least 55 m 2 Excellent results were obtained with a combination of 100% to 200% industrial carbon black.

[0107] To achieve these advantages, the present invention requires a purposeful selection of special fillers F1. Among them, HTT lignin has proven to be particularly suitable because they have excellent compatibility with the other components of the rubber composition and with the special vulcanization system described below, in particular, they can achieve the desired gas barrier properties and reduce crack formation and crack propagation.

[0108] The fillers F1 used according to the invention, and in particular the HTT lignin used in the invention, allow a good balance of different properties to be adjusted with regard to the use in the liner. They therefore have good reinforcing properties, expressed in terms of stress values ​​and tear strength of the vulcanized rubber, high elongation at break of the rubber, and they also promote a good dispersibility of the filler particles in the rubber. In particular, their use, especially in large amounts, leads to a significant reduction in the gas permeability of the vulcanized rubber and a reduction in crack propagation.

[0109] To achieve this, it is advantageous if the filler F1 used in the context of the present invention is preferably HTT lignin and has, in addition to the above-mentioned STSA surface area, a surface area of ​​40 m 2 / g to 100m 2 BET surface area in the range of 42 m / g, preferably 42 m 2 / g to 75m 2 / g, particularly preferably 44m 2 / g to 70m 2 / g.

[0110] It is preferred that the filler F1 used according to the invention, preferably HTT lignin, has a pH in the range from 7 to 10, particularly preferably in the range from 8 to 9.5.

[0111] It was also found that the ash content and heat loss had little effect, as long as these values ​​were not too high, thereby significantly reducing the content of active components.

[0112] As shown in the experimental part of the present application, the filler used herein, preferably HTT lignin, has the potential to completely replace carbon black in the production of rubber compositions, in particular those used for the production of innerliners, although the STSA surface area of ​​the filler F1 used herein is significantly higher than that of the industrial carbon blacks N660 and N772 commonly used in innerliners. This means that the preferred rubber compositions according to the present invention do not need to contain carbon black from materials of fossil origin.

[0113] This makes it possible in particular to produce innerliners for pneumatic tires having significantly reduced weight, improved air retention capacity and improved crack resistance, as well as reduced crack propagation, the same dimensions as similar innerliners obtained using carbon black. In particular, the better air retention capacity ensures that the rolling resistance of the tire is at an optimal level for a longer period of time, thus enabling vehicles equipped with such tires to run more economically.

[0114] However, it is also possible to replace only a portion of the carbon black in the fossil-derived material with one or more fillers F1 usable according to the invention, preferably HTT lignin. The F2 carbon blacks described below are particularly advantageous in this respect, although in particular their STSA surface far exceeds the specifications of the carbon blacks usually used for linings. This also introduces new fields of application for the industrial carbon blacks F2.

[0115] Other components of the rubber composition

[0116] Filler F2 (= Industrial carbon black F2)

[0117] In addition to the above-mentioned mandatory filler F1 used according to the invention, preferably HTT lignin F1, the rubber composition may also contain other filler F2 components different from F1 in the filler component, namely industrial carbon black having the above-mentioned specifications

[0118] The calculation of the weighted arithmetic mean of the STSA surface area for the technical carbon black F2 was the same as described for filler F1.

[0119] The weighted arithmetic mean of the STSA surface area of ​​industrial carbon black F2 is 55 m 2 / g to 95m 2 / g, preferably within 60 m 2 / g to 92m 2 / g, particularly preferably 65 m 2 / g to 91m 2 / g, more preferably in the range of 70 m 2 / g to 85m 2 / g range, especially 72m 2 / g to 80m 2 / g.

[0120] Preferably, each individual industrial carbon black F2 (i.e. filler F2) has a STSA surface area of ​​55 m 2 / g to 95m 2 / g, particularly preferably 65 m 2 / g to 90m 2 / g, more preferably in the range of 70 m 2 / g to 85m 2 Of course, the selection of the individual fillers F2 is based on the mandatory requirement that the weighted arithmetic mean of the STSA surface areas of the fillers F2 is within the range mentioned in the previous paragraph.

[0121] Surprisingly, it has been found that the use of the technical carbon black F2 characterized as above has advantages in terms of higher tensile strength and, in particular, higher elongation at break. In particular, the small aggregate size appears to have a positive effect on crack growth, since more particles and therefore more defects within the same unit volume may counteract crack growth.

[0122] The surface area of ​​STSA used in lining production is 34m 2 / g and 28m 2Compared with the partial replacement of filler F1 by carbon black N660 and N772, the industrial carbon black F2 characterized above allows to provide 55m 2 / g to 95m 2 The STSA surface area is preferably in the range of 65 m / g. 2 / g to 90m 2 / g, more preferably in the range of 70 m 2 / g to 85m 2 / g range.

[0123] For example, carbon black N326 contains smaller aggregates than semi-activated carbon blacks N660 and N772 due to a higher specific surface area (STSA). The inventors assume that there are more particles per unit volume at the same dosage, which improves the physical interaction and produces a higher reinforcement effect. This seems to be particularly beneficial in terms of dynamic crack resistance.

[0124] Preferred industrial carbon blacks F2 are those listed in the ASTM D1765 standard under the designation N3XX. These include, in particular, industrial carbon blacks under the designations N326, N330, N347, N339, N375 and N351.

[0125] Filler F2 is never used alone but always at least in combination with filler F1 in the filler component. However, when filler F2 is used, the amount of filler F1 is more than 35 phr, preferably at least 36 phr, particularly preferably at least 38 phr, such as at least 40 phr.

[0126] In the case of using other fillers F2 having the above-mentioned characteristics, their content is preferably less than 25 phr, more preferably from 1 phr to 25 phr, more preferably from 5 phr to 20 phr, and most preferably from 8 phr to 18 phr.

[0127] Preferably, the sum of the amounts of filler F1 and technical carbon black F2 is at least 45 phr, more preferably from 45 phr to 80 phr, more particularly preferably from 45 phr to 70 phr, even more preferably from 45 phr to 60 phr.

[0128] The content of filler F1 in the sum of all fillers F1 plus F2 is preferably 50% to 100% by weight, more preferably 65% ​​to 100% by weight, very particularly preferably 80% to 100% by weight.

[0129] The weighted arithmetic mean of the STSA surface areas of the sum of the filler F1 and the technical carbon black F2 is at least 40 m 2 / g, particularly preferably 45m 2 / g to 65m 2 / g, more preferably 47m 2 / g to 63m 2 / g, even more preferably 50m 2 / g to 60m 2 / g.

[0130] Filler F3

[0131] In addition to filler F1 and optionally present filler / industrial carbon black F2, the rubber composition of the present invention may also comprise other fillers F3 that do not fall within the definition of fillers F1 and F2. These are in particular inorganic fillers of different particle diameters, particle surface areas and chemical properties, with different possibilities for influencing the vulcanization behavior. In the case of comprising other fillers, these fillers should preferably have properties as similar as possible to the fillers F1 and F2 used in the rubber composition of the present invention.

[0132] If other fillers F3 are used, they are preferably phyllosilicates, such as clay minerals, for example talc; carbonates, such as calcium carbonate; and silicates, such as calcium silicate, magnesium silicate and aluminum silicate. However, they can also be fillers F3, each of which has a carbon content of less than 40 m 2 / g or greater than 80m 2 / g STSA surface area, and 14 The specifications of filler F1 are met in terms of C content and carbon content, and preferably also in terms of particle size distribution and acidic hydroxyl groups. However, filler F3 can also be a filler with a STSA surface area of ​​less than 55 m 2 / g or greater than 95m 2 / g of industrial carbon black F3.

[0133] Inorganic fillers, wherein preferred silicon dioxide and other fillers (with Si-OH groups on their surfaces), can also be surface treated. Particularly, it may be advantageous to carry out salification with organosilane (for example alkyl alkoxysilane or aminoalkyl alkoxysilane or mercaptoalkyl alkoxysilane). For example, alkoxysilane groups can be attached to the surface of silicate or silicon dioxide by hydrolysis condensation, or attached on other suitable groups, and amino and mercapto, for example, can react with the halogenation of halogenated butyl rubber, particularly brominated isoprene units. This can cause the mechanical reinforcement of vulcanized rubber composition of the present invention.

[0134] The use of salted fillers can accelerate the final state of cure and improve edge tear resistance.

[0135] The fillers may be used alone or in combination.

[0136] Preferably, in addition to the fillers F1, in particular HTT lignin F1, and any other fillers F2 optionally present therein according to the invention, no fillers F3 are used or only small amounts are used. If other fillers F3 are used, these are preferably industrial carbon blacks F3 which do not fall within the definition of industrial carbon blacks F2, or phyllosilicates, such as clay minerals, for example talc. The content of fillers F3 in the filler component is preferably less than 40 phr, particularly preferably from 0 phr to 25 phr, very particularly preferably from 0 phr to 15 phr.

[0137] Softener

[0138] By using softeners, it is possible to influence the properties of the unvulcanized rubber composition, such as in particular the processing properties, but also the properties of the vulcanized rubber composition, such as the flexibility, in particular at low temperatures.

[0139] In the context of the present invention, particularly suitable softeners are mineral oils from the group of paraffinic oils (essentially saturated chain hydrocarbons) and naphthenic oils (essentially saturated cyclic hydrocarbons). The use of aromatic hydrocarbon oils is possible, but less advantageous, because their dissolution behavior with halogenated butyl rubber is poor. However, with regard to the adhesion of the rubber composition to other rubber-containing parts in the tire (such as the carcass), a mixture of paraffinic oils and / or naphthenic oils may be advantageous as a softener.

[0140] Other softeners are, for example, esters of aliphatic dicarboxylic acids, such as adipic acid or sebacic acid, paraffin waxes and polyethylene waxes.

[0141] Among the softeners, paraffinic oils and naphthenic oils are particularly suitable in the context of the present invention.

[0142] Preferably, the softener, of which paraffin oil and / or naphthenic oil is more particularly preferred, is used in an amount of 0 to 20 phr, preferably 5 to 15 phr, particularly preferably 7 to 13 phr.

[0143] Adhesion enhancing resins (“tackifying resins”)

[0144] So-called adhesion-enhancing resins may be used to improve the adhesion of the cured rubber compounds of the present invention to other adjacent tire components.

[0145] Particularly suitable resins are phenol-based resins, preferably from the group consisting of phenol-formaldehyde resins, phenol-formaldehyde resins and phenol-acetylene resins.

[0146] In addition to phenol-based resins, aliphatic hydrocarbon resins, such as ExxonMobil's EscorezTM 1102RM, and aromatic hydrocarbon resins can also be used. Aliphatic hydrocarbon resins specifically improve adhesion to other rubber components of the tire. They generally have lower adhesion than phenol-based resins and can be used alone or in combination with phenol-based resins.

[0147] If adhesion-enhancing resins are used, preferably those selected from the group consisting of phenol-based resins, aromatic hydrocarbon resins and aliphatic hydrocarbon resins are used. Preferably, their amount is 0 to 15 phr or 1 to 15 phr, particularly preferably 2 to 10 phr, more particularly preferably 3 to 8 phr.

[0148] Additives that promote vulcanization

[0149] The rubber composition according to the present invention can also contain additives that promote vulcanization, but cannot start vulcanization on its own. These additives include, for example, vulcanization accelerators, such as saturated fatty acids with 12 to 24, preferably 14 to 20, and particularly preferably 16 to 18 carbon atoms, such as stearic acid and the zinc salt of the above-mentioned fatty acid. Thiazoles may also belong to these additives. However, it is also possible to use vulcanization accelerating additives only in the following vulcanization system.

[0150] If vulcanization accelerating additives are used in the rubber composition of the invention, in particular the above-mentioned fatty acids and / or their zinc salts, preferably stearic acid and / or zinc stearate, their amount is preferably 0 to 5 phr, particularly preferably 0.5 to 3 phr, particularly preferably 1 to 2 phr.

[0151] It is preferred that the rubber composition of the present invention contains, in addition to the essential ingredients, one or more components selected from the group consisting of the following components:

[0152] i. Rubber other than halogenated butyl rubber,

[0153] ii. Industrial carbon black F1 and / or filler F3,

[0154] iii. Softener,

[0155] iv. Adhesion enhancing resins, and

[0156] v. Additives that promote vulcanization.

[0157] If it contains one or more of the ingredients mentioned in items i. to v. above, then

[0158] i. preferably a rubber selected from the group consisting of natural rubber, butyl rubber and styrene-butadiene rubber,

[0159] ii. is a filler F2 as defined above or a filler F3 selected from the group of carbon blacks different from F2 and layered silicates, iii. is preferably an ester of an aliphatic dicarboxylic acid, a paraffin oil and / or a naphthenic oil,

[0160] iv. a resin selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins and phenol acetylene resins; and

[0161] v. is an additive selected from the group consisting of saturated fatty acids having 12 to 24 carbon atoms and thiazoles.

[0162] If components i. to v. are included, they are preferably included in the following amounts:

[0163] i. 0 phr to 40 phr, particularly preferably 0 phr to 30 phr, more particularly preferably 0 phr to 20 phr or 0 phr;

[0164] ii. 0 phr to 40 phr, more preferably 0 phr to 25 phr, particularly preferably 0.1 phr to 20 phr, more particularly preferably 0.5 phr to 18 phr;

[0165] iii. 0 to 20 phr, particularly preferably 5 to 15 phr, more particularly preferably 7 to 13 phr;

[0166] iv. 0 to 15 phr, particularly preferably 2 to 10 phr, more particularly preferably 3 to 8 phr; and

[0167] v. 0 to 5 phr, particularly preferably 0.5 to 3 phr, very particularly preferably 1 to 2 phr.

[0168] Vulcanizable rubber composition

[0169] The vulcanizable rubber composition of the present invention comprises the rubber composition of the present invention and a vulcanization system for vulcanization thereof.

[0170] Vulcanization system

[0171] The vulcanization system is not contained in the rubber composition of the invention here, but is treated as an additional system for regulating its crosslinking.By adding the vulcanization system to the rubber composition of the invention, the vulcanizable rubber composition of the invention is also obtained.

[0172] The rubber composition of the present invention based on halogenated butyl rubber allows the use of a variety of different vulcanization systems. Chlorine-carbon bonds, but especially bromine-carbon bonds, which are weaker than carbon-carbon bonds, can be vulcanized faster and co-vulcanize better with general-purpose rubbers.

[0173] The vulcanization of the rubber composition of the present invention is preferably carried out using zinc oxide and / or sulfur.

[0174] In the preferred variants described below, zinc oxide is preferably used for the vulcanization in combination with various organic compounds. By means of various additives, the vulcanization behavior and the properties of the vulcanizates obtained therefrom can be influenced.

[0175] In the first variant of zinc oxide-based vulcanization, small amounts of saturated fatty acids having 12 to 24, preferably 14 to 20, particularly preferably 16 to 18 carbon atoms, such as stearic acid and / or zinc stearate, are preferably added to the zinc oxide as vulcanization accelerators. This allows the vulcanization rate to be increased. However, the use of the above-mentioned fatty acids in most cases reduces the final grade of the vulcanization.

[0176] In a second variant of zinc oxide-based vulcanization, so-called thiurams such as thiuram monosulfide, thiuram disulfide and / or dithiocarbamates are added to zinc oxide in the absence of sulfur to shorten the scorch time and improve the vulcanization efficiency by forming a particularly stable network.

[0177] In a third variation of zinc oxide based vulcanization, alkylphenol disulfide is added to zinc oxide to adapt the scorch time, in particular to accelerate the scorch time.

[0178] Another variant of zinc oxide-based vulcanization, the fourth variant, uses zinc oxide in combination with polymethylolphenol resins and their halogenated derivatives, wherein neither sulfur nor sulfur-containing compounds are used.

[0179] In the other, the fifth variant of zinc oxide based vulcanization, vulcanization is carried out by the combination of zinc oxide and thiazole and / or sulfenamide and preferably sulphur.Thiazole and sulfenamide are preferably selected from the group consisting of 2-mercaptobenzothiazole (MBT), mercaptobenzothiazole disulfide (MBTS), N-cyclohexyl-2-benzothiazolyl sulfenamide (CBS), 2-morpholino-thiobenzothiazole (MBS) and N-tert-butyl 2-benzothiazolyl sulfenamide (TBBS).Adding sulphur to this system can improve vulcanization rate and degree of vulcanization, and contribute to the processability of rubber composition in vulcanization process.With the rubber different from halogenated butyl rubber, especially the co-vulcanization of above-mentioned rubber is also favourable.Use this vulcanization system preferably to provide heat-resistant and fatigue-resistant vulcanized materials, even under vulcanized state, these materials can also show good adhesion with other parts of vehicle tire, particularly the rubber composition of carcass. Particularly advantageous vulcanization systems comprise zinc oxide, thiazoles, such as preferably mercaptobenzothiazolyl disulfide (MBTS), and sulfur. Particularly preferred is the combination of the first variant with the fifth variant, i.e. a vulcanization system comprising zinc oxide, thiazoles, such as preferably mercaptobenzothiazolyl disulfide (MBTS), sulfur, and stearic acid and / or optionally zinc stearate.

[0180] Less preferred vulcanization systems are based on pure sulfur vulcanization or peroxide vulcanization, the latter of which may lead to an undesirable reduction in molecular weight due to cleavage of the molecules, in particular when butyl rubber or other rubbers are also used.

[0181] In the context of the present invention, the vulcanization of the rubber composition according to the invention is carried out in the presence of a specific filler F1, preferably a specific HTT lignin and optionally an industrial carbon black F2. The excellent properties of the vulcanized rubber composition according to the invention, in particular its suitability as an inner liner, are essentially based on the combination of a suitable rubber component with a specific filler F1, in particular the preferred HTT lignin F1 and optionally a specified amount of F2, with a zinc oxide-based vulcanization system, preferably a vulcanization system of the variant referred to above as the fifth variant, and even more preferably a combination of the first variant with the fifth variant.

[0182] Components of the vulcanization system which are not able to initiate vulcanization themselves may also be contained in the rubber composition according to the invention as "other components of the rubber composition". Thus, in particular stearic acid and / or optionally zinc stearate and / or thiazole compounds may already be present in the rubber composition and the complete vulcanization system may be formed in situ by the addition of zinc oxide and sulfur.

[0183] Complete set of parts

[0184] Due to the relationship between the rubber composition according to the present invention and the cross-linking system selected for its vulcanization, the invention further relates to a complete set of parts comprising rubber composition according to the present invention and vulcanization system (preferably zinc oxide and / or sulfur-based vulcanization system). In the complete set of parts, the rubber composition according to the present invention and vulcanization system are separated from each other spatially, and therefore can be stored. This complete set of parts is used to prepare a vulcanizable rubber composition. For example, the rubber composition according to the present invention constituting a part of a complete set of parts can be used as the part (A) in the step 1 of the method for preparing a vulcanizable rubber compound, and the second part of the complete set of parts, i.e. vulcanization system, can be used as the part (B) in the described method step 2.

[0185] Preferably, the kit comprises,

[0186] The rubber composition according to the present invention as part (A), and

[0187] As part (B) a vulcanization system comprises zinc oxide and / or sulfur.

[0188] Particularly preferably, the kit comprises,

[0189] The rubber composition according to the present invention as part (A), and

[0190] A vulcanization system comprising zinc oxide, sulfur and thiazole as part (B); or

[0191] a rubber composition according to the invention comprising thiazole as part (A), and

[0192] As part (B) a vulcanization system comprises zinc oxide and / or sulfur.

[0193] More particularly preferably, the kit comprises

[0194] The rubber composition according to the present invention as part (A), and

[0195] a vulcanization system comprising zinc oxide, sulfur, thiazole and stearic acid and optionally zinc stearate as part (B); or

[0196] a rubber composition according to the invention comprising, as part (A), stearic acid and optionally zinc stearate, and

[0197] A vulcanization system comprising zinc oxide, sulfur and thiazole as part (B).

[0198] The preferred thiazole in the above-mentioned component parts is MBTS.

[0199] In contrast to vulcanizable rubber compositions which already comprise the components of the rubber composition according to the invention and the components of the associated vulcanizing system in the form of a homogeneous mixture, so that the vulcanizable rubber composition can be vulcanized directly, the rubber composition according to the invention and the vulcanizing system are spatially separated in the kit.

[0200] The vulcanizable rubber composition obtainable from the kit is also referred to herein as an "unvulcanized compound." It can be obtained by the two-stage process described in the next section.

[0201] Method for preparing the rubber composition of the present invention and vulcanizable rubber composition prepared therefrom

[0202] The preparation of the vulcanizable rubber compound is preferably carried out in two stages.

[0203] In the first stage, the rubber composition of the present invention is first prepared as a base compound (masterbatch) by compounding the components of the rubber composition. In the second stage, the components of the vulcanization system are mixed.

[0204] Phase 1

[0205] Preferably, halogenated butyl rubber and any other rubber used optionally, and any adhesion enhancing resin used optionally, are provided. However, the latter can also be added together with other additives. Preferably, the rubber has at least room temperature (23° C.), or is used after being preheated to a temperature not exceeding 50° C., preferably not exceeding 45° C., particularly preferably not exceeding 40° C. It is particularly preferred that the rubber is pre-crushed for a short time before the other components are added. If inhibitors such as magnesium oxide are used for subsequent vulcanization control, they are preferably also added at this time.

[0206] Subsequently, the filler F1 used according to the invention, preferably HTT lignin, and optionally further fillers F2 and / or F3, preferably with the exception of zinc oxide, are added, since it is used as a component of the vulcanization system in the rubber composition according to the invention and is therefore not considered as a filler in this context. The addition of the filler F1 used according to the invention, preferably HTT lignin, and optionally further fillers F2 and / or F3 is preferably carried out stepwise.

[0207] Advantageously, but not necessarily, the softener and other components, such as stearic acid and / or zinc stearate, are added only after the addition of the filler F1, preferably HTT lignin, or other fillers F2 and / or F3, if used, used according to the invention. This facilitates the incorporation of the filler F1, preferably HTT lignin, and other fillers F2 and / or F3, if present, used according to the invention. However, it may be advantageous to add part of the filler F1, preferably HTT lignin, or other fillers F2 and / or F3, if present, used according to the invention together with the softener and any other components optionally used.

[0208] The maximum temperature obtained during the first stage preparation of the rubber composition ("dumping temperature") should not exceed 140°C, because above these temperatures there is a risk of partial decomposition of the reactive halogenated butyl rubber. Preferably, the maximum temperature during the first stage preparation of the rubber composition is from 100°C to 130°C, particularly preferably from 105°C to 120°C.

[0209] The mixing of each component of the rubber composition according to the present invention is usually carried out by an internal mixer equipped with a tangential or meshing (i.e., intermeshing) rotor. The latter usually allows better temperature control. However, mixing can also be carried out using, for example, a double-roll mixer.

[0210] After the rubber composition is prepared, it is preferably cooled before proceeding to the second stage. This type of process is also called aging. The typical aging period is 6 hours to 24 hours, preferably 12 hours to 24 hours.

[0211] Phase 2

[0212] In the second stage, the components of the vulcanization system are incorporated into the rubber composition of the first stage, thereby obtaining a vulcanizable rubber composition according to the invention.

[0213] If a zinc oxide-based vulcanization system is used as the vulcanization system, zinc oxide and other components, such as in particular sulfur and particularly preferably thiazole, are added in stage 2.

[0214] The maximum temperature ("dump temperature") obtained during the preparation of the mixture of the vulcanization system and the rubber composition in the second stage should preferably not exceed 110° C., particularly preferably not exceed 105° C. The preferred temperature range is 90° C. to 110° C., particularly preferably 95° C. to 105° C. At temperatures above 105° C. to 110° C., premature vulcanization may occur.

[0215] After mixing the vulcanization system in stage 2, the composition is preferably cooled.

[0216] In the two-stage process described above, a rubber composition according to the invention is therefore first obtained in a first stage, which is supplemented in a second stage to form a vulcanizable rubber composition, in particular a vulcanizable rubber composition for an inner liner.

[0217] Method for further processing of the vulcanizable rubber composition according to the invention

[0218] The vulcanizable rubber composition obtained in the above two-stage process is preferably further processed by calendering, extrusion or roll head process.

[0219] Calendering

[0220] The vulcanizable rubber composition of the present invention is preferably fed to a calender in the first step (a), for example using a preheating mill and a downstream feeding mill, or fed during extrusion using an extruder. In both cases, before the vulcanizable rubber composition is fed to the calender, its temperature should preferably be 65° C. to 85° C., particularly preferably 70° C. to 80° C.

[0221] In the second step (b), calendering is carried out, wherein different roll positions of preferably three or four rolls of the calender are possible. Preferably, calendering is carried out by means of a four-roller Z-calender ("inclined Z-calender") or a four-roller L-calender ("inverted L-calender"). Here, the temperature of the cooler pick-up roll is preferably 75° C. to 85° C., while the temperature of the hotter roll is preferably 85° C. to 95° C.

[0222] After calendering, the calendered vulcanizable rubber composition leaves the calender in a third step (c) as a calender web and is cooled, preferably to a temperature below 35° C., before subsequent processing. It is also possible to combine several calender webs into multiple layers when the calender web leaves the calender. Care must be taken to ensure that no undesirable air inclusions occur during the combining process.

[0223] After the three steps, in the fourth step (d), the calendered web or the calendered web combined into multiple layers is advantageously stored for at least 3 hours, even better for at least 4 hours, preferably for at least 12 hours to 24 hours. This storage is for complete cooling of the calendered web and for allowing stress relaxation.

[0224] The calendering is preferably carried out at a calendering speed in the range of 20 m / min to 35 m / min, particularly preferably 25 m / min to 30 m / min.

[0225] Extrusion

[0226] In addition to calendering, linings can also be obtained by extrusion.

[0227] The feeding of the vulcanizable rubber composition of the present invention to the extruder is preferably carried out in the first step (a), for example by means of a two-roll mixer or other suitable feeding device. Here, before the vulcanizable rubber composition is fed to the calender, its temperature should preferably be 65° C. to 85° C., particularly preferably 70° C. to 80° C.

[0228] In the second step (b) of extrusion, temperatures of 100° C. may be achieved. Therefore, special care must be taken to ensure that burning does not occur.

[0229] After extrusion, the extruded vulcanizable rubber composition leaves the extruder as a web in a third step (c) and is cooled, preferably to a temperature below 35° C., before subsequent processing. When the web leaves the extruder, multiple webs may also be combined into multiple layers. Care must be taken to ensure that undesirable air inclusions do not occur during the combining process.

[0230] After the three steps, in the fourth step (d), the web or the webs combined into multiple layers are advantageously stored for at least 3 hours, even better for at least 4 hours, preferably for at least 12 hours to 24 hours. This storage is for complete cooling of the web and allows stress relaxation.

[0231] Roller head process

[0232] Unlike the above-mentioned multi-roll calendering, in the roller head process, the calendering nip of the two-roll or three-roll calender is fed with the rubber compound by an extruder with a preforming head. The extruder itself can be fed with warm raw materials or cold raw materials. For example, a cold feed pin extruder can be used. When the provided compound matches the web to be calendered in terms of thickness and width, the feed of the roller gap (calendering nip) can be optimized, which can be achieved by selecting a preforming head and a replaceable forming die mounted at its end.

[0233] In terms of operating behavior, roller-headlines are located between extruders and calenders, where uniform flow in the extruder die is critical for the quality and dimensions of thicker webs, and calendering behavior is more important for thinner webs.

[0234] The operating temperatures are within the ranges described above for calendering and extrusion for these processes.

[0235] As already mentioned in connection with calendering, according to step (c) above, the finished web has to be cooled after leaving the calender, preferably followed by step (d) above.

[0236] The vulcanizable web obtained by calendaring, extrusion or by the roll head process has a layer thickness of 0.3 mm to 5 mm, particularly preferably 0.4 mm to 4 mm, very particularly preferably 0.5 mm to 3 mm. These layer thickness ranges are typical values ​​for inner liners.

[0237] Vulcanized rubber composition

[0238] Another object of the present invention is a vulcanized rubber composition obtainable from the above-described vulcanizable rubber composition, for example also by using a kit of parts.

[0239] The vulcanization conditions depend on the vulcanization system used. The suitable vulcanization temperature is preferably 140°C to 200°C, particularly preferably 150°C to 180°C.

[0240] Preferably, the vulcanized rubber composition is an inner liner of a pneumatic tire.

[0241] Properties of the vulcanized rubber compositions

[0242] The vulcanized rubber composition obtained from the vulcanizable rubber composition according to the present invention preferably has

[0243] (a) a Shore A hardness in the range of 35 to 65, particularly preferably 38 to 60 and very particularly preferably 40 to 55; and / or

[0244] (b) a modulus 300 of 2.8 MPa to 8 Pa, particularly preferably 3.0 MPa to 6.0 MPa, and more particularly preferably 3.0 MPa to 4.0 MPa; and / or

[0245] (c)1.000g / cm 3 Up to 1.120g / cm 3 The density is preferably 1.010 g / cm 3 Up to 1.100g / cm 3 And more preferably 1.020 g / cm 3 Up to 1.080g / cm 3 ; and / or

[0246] (d) Less than 3.8 x 10 -17 m 2 / Pas gas permeability, and a particularly preferred gas permeability is 2.5 x 10 -17 m 2 / Pas to 3.8x 10 -17 m 2 / Pas, and more particularly preferably 2.7 x 10-17 m 2 / Pas to 3.7x 10 -17 m 2 / Pas, such as 2.8x10 -17 m 2 / Pas to 3.5x 10 -17 m 2 / Pas.

[0247] In general, higher contents of fillers F1 that can be used according to the invention, in particular HTT lignin and optionally other fillers, generally further reduce the gas permeability, but at the expense of the tear strength and tear elongation of the composite. By partially replacing filler F1 with industrial carbon black F2, both the tensile strength and the elongation at break can be greatly improved without significantly deteriorating the other properties.

[0248] Method for manufacturing a pneumatic tire comprising an inner liner made of a vulcanizable rubber composition according to the present invention

[0249] The vulcanizable web obtainable by the above method is preferably stored in the form of a roll before use and used as an inner lining material in the manufacture of pneumatic tires. For this purpose, the web must be cut into drum circumferences, which can be achieved by using an ultrasonic knife or a heated rotating circular knife, the latter preferably using a so-called roll-on-and-cut process.

[0250] The innerliner is typically cured under pressure and / or heat along with the tire carcass and / or other tire components.

[0251] The suitable vulcanization temperature is preferably 140°C to 200°C, particularly preferably 150°C to 180°C.

[0252] The process can be carried out, for example, by closing the press and shaping the green tire into a closing mound. For this purpose, the inner bellows (heating bellows) can be pressurized with a low pressure (<0.2 bar) so that the bellows can also be installed in the green tire. After that, the press and the mound are completely closed. The pressure in the bellows increases (to the shaping pressure, usually about 1.8 bar). As a result, the profile is imprinted on the tread and sidewall labels. In the next processing step, the press is locked and the clamping force is applied. The clamping force varies depending on the type of press and the size of the tire and can reach up to 2500 kN when using hydraulic cylinders. After the closing force is applied, the actual vulcanization process begins. Here, the mold is continuously heated with steam from the outside, wherein the temperature is usually set at 150°C to 180°C. For the internal medium, there are several different variants depending on the type of tire. For example, steam or hot water is used in the heating bellows. The internal pressure may vary and differ depending on the type of tire, such as passenger car or truck tires.

[0253] All measured quantities related to the present invention mentioned in this specification were determined according to the procedures mentioned in the Experimental Section.

[0254] Use of fillers F1 used according to the invention, in particular HTT lignin F1, and mixtures of F1 and F2

[0255] Another object of the present application is the use of a filler F1 as defined above and of a rubber composition according to the invention, preferably HTT lignin, or a mixture of filler F1 and technical carbon black F2 (these are also defined above), in a rubber composition for innerliners, wherein the total amount of filler F1 and technical carbon black F2 is at least 46 phr.

[0256] This use is particularly intended to reduce gas permeability and crack propagation, especially compared to rubber compositions containing technical carbon black N660 and / or technical carbon black N772 instead of F1 and / or F2.

[0257] Example

[0258] The components of the rubber composition, the unvulcanized rubber composition, and the vulcanized rubber composition were subjected to various testing procedures, which are described in more detail below.

[0259] Characterization of fillers F1 and F2

[0260] Mass-related surfaces (BET surfaces and STSA surfaces)

[0261] The specific surface area of ​​HTT lignin is determined by nitrogen adsorption according to the ASTM D 6556 (2019-01-01) standard provided for industrial carbon black. According to this standard, the BET surface area (according to the total surface area of ​​Brunauer, Emmett and Teller) and the external surface area (STSA surface area; statistical thickness surface area) are determined as follows.

[0262] Before the measurement, the sample to be analyzed is dried at 105°C to a dry matter content of ≥ 97.5% by weight. In addition, before weighing the sample, the measuring cell is dried in a drying oven at 105°C for several hours. The sample is then filled into the measuring cell using a funnel. If the shaft of the upper measuring cell is contaminated during the filling process, it is cleaned with a suitable brush or pipe cleaner. In the case of strongly flying (static) material, glass wool is additionally weighed into the sample. Glass wool is used to retain any material that may fly up and contaminate the device during the baking process.

[0263] The sample to be analyzed was baked at 150℃ for 2 hours. 2 O 3 The standard was baked at 350°C for 1 hour.

[0264] Depending on the pressure range, use the following N2 Dosage determination:

[0265] p / p0=0-0.01:N 2 Dosage: 5ml / g

[0266] p / p0=0.01-0.5:N 2 Dosage: 4ml / g

[0267] To determine the BET, extrapolation was performed in the range of p / p0 = 0.05 to 0.3 with at least 6 measurement points. To determine the STSA, the adsorption of N 2 Extrapolation was performed in the layer thickness range from t = 0.4 nm to 0.63 nm (corresponding to p / p0 = 0.2 to 0.5) with at least 7 measuring points.

[0268] Determination of pH

[0269] As described below, pH value is determined according to ASTM D 1512 standard. If the dry sample is not yet in powder form, it is mortared or ground into powder. In each case, 5g sample and 50g completely deionized water are weighed into a glass beaker. The suspension is heated to a temperature of 60°C under constant stirring using a magnetic stirrer with a heating function and a stirring rod (stirring flea), and the temperature is maintained at 60°C for 30 minutes. Subsequently, the heating function of the stirrer is deactivated so that the mixture is cooled while stirring. After cooling, the evaporated water is replenished by adding completely deionized water again and stirring again for 5 minutes. The pH value of the suspension is measured with a measuring instrument. The temperature of the suspension should be 23°C (± 0.5°C). Each sample is measured repeatedly and the average value is reported.

[0270] Determination of bulk density

[0271] The bulk density of the sample is determined according to ISO 697 as described below. A standard beaker (100 ml volume) conforming to DIN ISO 60 for determining the bulk density is placed in a pan to collect the overflow. The beaker is filled to overflow using a funnel and a shovel. The excess is scraped off along the hole of the beaker with the ruler of the shovel. The outside of the beaker is wiped with a dry cloth and then weighed with an accuracy of 0.1 g.

[0272] Determination of available acidic hydroxyl groups on the surface (OH group density)

[0273] According to Sipponen, the determination of surface-accessible acidic hydroxyl groups is carried out qualitatively and quantitatively by colorimetry. The method according to Sipponen is based on the adsorption of the basic dye Azure B onto the surface-accessible acidic hydroxyl groups of the filler and is described in detail in the paper "Determination of surface-accessible acidic hydroxyls and surface area oflignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87). The amount of surface-accessible acidic hydroxyl groups is given in mmol / g filler. Regardless of how the filler is obtained, the process is not only applicable to lignin-based fillers, but also to, for example, the comparative carbon black N660.

[0274] 14 Determination of C content

[0275] 14 The C content (biobased carbon content) can be determined by the radiocarbon method in accordance with DIN EN 16640:2017-0.

[0276] Determination of particle size distribution

[0277] The particle size distribution can be determined according to ISO 13320:2009 by laser diffraction of the material dispersed in water (1 wt. % in water), whereby an ultrasonic treatment of 12000 Ws is carried out before the measurement. The volume fraction is designated as D v (97), in μm (97% of the sample volume has a particle diameter below this value). The same method is also applicable to D v (50) value.

[0278] Characterization of the vulcanizable rubber composition ("unvulcanized compound")

[0279] Determination of reaction kinetics / vulcanization kinetics

[0280] The reaction kinetics of the non-vulcanized rubber compound ("unvulcanized compound") was determined by measuring the time course of torque [dNm] using a rheometer MDR3000 Professional (MonTech Werkstoffprüfmaschinen GmbH, Buchen, Germany) according to DIN53529Tl 3 (torsion shear rotorless vulcanizer). The upper and lower rotor plates of the rheometer were heated to 160 ° C. 5.5 g ± 0.5 g of the non-vulcanized rubber composition was cut from the center of the sheet with scissors. Here, care was taken to ensure that the cutout represented a square area and that the diagonal of the area corresponded to the diameter of the rheometer rotor. Before the non-vulcanized rubber composition was placed on the rotor of the rheometer, the top and bottom of the cutout were covered with a film. After the unvulcanized sample was inserted, the measurement was started immediately.

[0281] The minimum and maximum torques (M) were determined from the measurement curves during a 30-minute test period at 160°C (0.5° arc, 1.67 Hz). L , M H ), and calculate the difference Δ(M H -M L ).

[0282] In addition, for each measurement curve, the minimum torque M L Defined as the maximum torque M H 0%, maximum torque M H is normalized to 100%. Subsequently, the minimum torque M is determined L The starting torque reaches the maximum torque M H The time periods are designated as T 10 , T 50 and T 90 .

[0283] Characterization of vulcanized rubber compositions

[0284] Determination of Shore A hardness

[0285] The mensuration of the Shore A hardness of the vulcanized rubber composition is carried out according to ISO 7619-1 using the digital Shore durometer of Sauter GmbH company.Before each measurement, the instrument is calibrated using the calibration plate attached.In order to measure the hardness, three S2 rods punched out and carried out tensile test according to DIN 53504 are stacked on each other.Hardness measurement is carried out at five different positions of the stacked object.The Shore A hardness of the vulcanized rubber composition represents the mean value of five measurements.Between vulcanization and test, the sample is stored at room temperature for at least 16 hours in the laboratory.

[0286] Determination of density of vulcanized rubber compositions

[0287] The determination of the density of the vulcanized rubber composition is carried out according to DIN EN ISO 1183-1:2018-04 (method for determining the density of non-foamed plastics) method A (immersion method). Ethanol is used as an immersion medium. The density of the vulcanized rubber composition represents the average value of three determinations. Between vulcanization and testing, the samples are stored in the laboratory at room temperature for at least 16 hours.

[0288] Determination of gas permeability

[0289] The determination of the gas permeability of the vulcanized rubber compositions to air is carried out in accordance with ISO 15105. The measurements are carried out at 70° C. The gas permeability represents the average of three measurements. Between vulcanization and testing, the samples are stored in the laboratory at room temperature for at least 16 hours.

[0290] Determination of compression set

[0291] The compression set of vulcanized rubber compositions was determined according to DIN ISO 815-1:2016-09. Three test bodies were tested per sample. The exposure time was 22 hours and the compression set was measured from the moment the test body was placed in the heating cabinet. The test temperature was 70°C. The applied compressive stress was 25% of the initial thickness of the test body. Between vulcanization and testing, the test bodies were stored at room temperature for at least 16 hours.

[0292] Determination of tear strength, tear elongation and stress value (modulus)

[0293] Tensile testing is used to determine tear strength, tear elongation and stress values ​​of non-preloaded objects. In a tensile test, an object is stretched to tear at a constant strain rate and the force required and the change in length are recorded.

[0294] Tear strength: The tear strength σR is the quotient of the force FR measured at the moment of tearing and the initial cross-section A0 of the sample body.

[0295] Tensile strength: The tensile strength σmax is the quotient of the maximum force Fmax measured and the initial cross-section A0 of the sample body. For elastomers, the force FR generated during tearing is usually also the maximum force Fmax.

[0296] Tearing elongation: The tearing elongation εR is the quotient of the change in length LR-L0 measured at the moment of tearing and the original measured length L0 of the sample body. It is expressed as a percentage. For the sample bar used, L0 is the specified distance between the two measuring marks.

[0297] Stress value: The stress value σi is the tension Fi present when a certain elongation is reached, related to the initial cross-section A0. For a sample bar, the strain is related to the original measured length L0, i.e. the specified distance between the measuring marks.

[0298] The tensile strength, tear elongation and stress values ​​of the vulcanized rubber compositions were determined in accordance with ISO 37 using a testing instrument of the Tensor Check type from Gibitre Instruments. Between vulcanization and testing, the samples were stored in the laboratory at room temperature for at least 16 hours. For the determination of the modulus, at least five dumbbell test specimens were punched out of the vulcanized rubber compositions, the body dimensions of which were as given in ISO 37 (bar type S2). The thickness of the body of the specimens was determined using The thickness was determined using a calibrated thickness gauge from Messuhren and represents the average of three measurements made at different locations on the bridge section. The crosshead speed during the tensile test was 200 mm / min. The stated measured values ​​for tensile strength, elongation at break and stress values ​​(modulus 100, 200, 300) are the average of five measurements.

[0299] De Mattia crack growth test according to DIN 53522

[0300] In the fatigue bending test to evaluate the crack propagation resistance of elastomers, dynamic tests are performed using the De Mattia test apparatus. The test body (140 x 25 x 6.3 mm) has a transverse groove and is deformed by compression using an eccentric. There are 300 bending cycles per minute, whereby the test body is bent to 40% of the clamping length. The test body is pierced in the middle of the groove with a cutting tool described in the standard, thereby producing a 2 mm crack before the start of the test. The test is continued until the crack length changes significantly. The number of cycles is recorded within a certain extension range of the crack.

[0301] Volume swelling of toluene and M c Calculation

[0302] The crosslinked polymer swells in the solvent (LM) to a certain equilibrium value which is a function of the degree of crosslinking. This can be determined by the swelling elongation.

[0303] Therefore, the swelling behavior of the elastomer can be used to determine the average molecular network arc length M c , which is one of the most important structural parameters of the polymer network. This parameter is decisive for the mechanical properties of the elastomer.

[0304] M c Obtained from reaction: M c =A / B*q 5 / 3

[0305] M c = average molar mass between two cross-linking positions

[0306] A=rubber density*solvent molecular volume

[0307] B = 0.5-Flory-Huggins constant (here 0.35)

[0308] q = degree of swelling

[0309] The swelling degree q corresponds to the volume fraction q = 1 / v 2 The reciprocal value of . 2 Calculated by the following equation: 2 =1 / (1+V 1 / V 0 ), where V 1 is the volume of the solvent and V0 is the volume of the unswollen rubber. 1 / V 0 Use the following equation to calculate:

[0310] V 1 / V 0 =(m q –m o ) / ρ L / m 0 / ρ

[0311] m q = Mass of swollen rubber

[0312] m 0 =Mass of rubber before swelling

[0313] ρ L = density of solvent

[0314] ρ = density of rubber.

[0315] Preparation Example

[0316] Preparation of HTT lignin usable according to the invention

[0317] Three fillers F1A, F1B and F1C derived from renewable virgin resources can be characterized as shown in Table 1. The characterization results are compared with commercially available and ASTM standardized industrial carbon blacks of types N660, N772 and N326.

[0318] Fillers F1A, F1B and F1C were prepared by hydrothermal treatment of lignin, as described in detail in WO 2017 / 085278 A1.

[0319] A lignin-containing liquid was prepared for this purpose. First, water and lignin were mixed and a lignin-containing liquid with a dry organic matter content of 15% by weight was prepared. Then, lignin was mainly dissolved in the lignin-containing liquid. For this purpose, the pH value was adjusted by adding NaOH. The preparation of the solution was supported by vigorous mixing at 80°C for 3 hours. The lignin-containing liquid was then hydrothermally treated to obtain a solid. The prepared solution was heated to a reaction temperature of 220°C at 2K / min and maintained for a reaction period of 8 hours. This was followed by cooling. As a result, an aqueous solid suspension was obtained. The solid was mostly dehydrated and washed by filtering and washing. The subsequent drying and heat treatment were carried out in a fluidized bed under nitrogen, whereby the drying process was heated to 50°C at 1.5K / min and maintained for 2.5 hours, and then heated to a temperature of 190°C at 1.5K / min for heat treatment, maintained for 15 minutes and cooled again. The dried solid was deagglomerated with nitrogen on a reverse jet mill to D v (97) (determined according to the above-mentioned determination method) until the particle size given in Table 1.

[0320] Table 1

[0321]

[0322] 1 = Available acidic hydroxyl groups on the surface

[0323] Preparation of different rubber compositions (stage 1)

[0324] In a Haake Rheomix 3000S mixer from the company ThermoFisher equipped with a Banbury rotor, the rubber composition (base compound; masterbatch) was prepared as follows, the components and amounts being given in Table 2.

[0325] Before starting mixing, the mixing chamber was heated to 40° C. The amounts of the components were calculated in each case to give a filling level of the mixing chamber of 70%. All components were weighed in advance on a scale from the company Kern. After starting the rotor (50 rpm), the mixing chamber was loaded with rubber, the filling device to the mixing chamber was pneumatically locked, and mixing was carried out until a total mixing time of 1 minute. After that, the filling device of the mixing chamber was opened, 1 / 3 of the amount of filler and additives (0.15 phr MgO; 4 phr Escorez 1102) were added, the mixing chamber was closed again, and mixing was carried out until a total mixing time of 2 minutes. The filling of the mixing chamber was then opened, 1 / 6 of the amount of filler was added, then 1 / 2 of the amount of oil, then 1 / 6 of the amount of filler, the mixing chamber was closed again, and mixing was carried out until a total mixing time of 4 minutes. After that, the filling device of the mixing chamber was opened, 1 / 6 of the amount of filler was added, then 1 / 2 of the amount of oil, then 1 / 6 of the amount of filler was added, the mixing chamber was closed again, and mixing was carried out until a total mixing time of 6 minutes. After a total mixing time of 8 minutes, the mixing chamber was aerated. The spraying temperature was controlled by adjusting the speed. Spraying occurred after a total mixing time of 10 minutes and the temperature of the compound was measured.

[0326] After the mixing process, the compound is removed from the mixer, cooled and homogenized on a laboratory mill with a medium nip width. To this end, the compound is first passed through the nip once, the resulting composite sheet is rolled into a "doll" and dropped from above through the nip six times. The sheet is then cooled on a cooling table until the sheet reaches room temperature.

[0327] Table 2

[0328]

[0329] 1 Bromobutyl X Butyl BB 2230 from Arlanxeo

[0330] 2 Carbon black N660 from Lehmann und Voss

[0331] 3 Paraffin oil from Hansen und Rosenthal Tudalen 1927

[0332] # The highest temperature reached during mixing (“dumping temperature”)

[0333] Comparative Example V1 differs from Example B1 according to the invention in that industrial carbon black N660 is used in this example. In Comparative Example V2, the maximum amount of F1A (phr) allowed for HTT lignin is used according to the teaching of WO 2020 / 202125 A1.

[0334] Preparation of vulcanizable rubber composition (stage 2)

[0335] Vulcanizable "unvulcanized compounds" of Examples V1, V2 and B1 were prepared for each rubber composition by mixing a vulcanization system consisting of 1 phr zinc oxide, 0.5 phr sulfur and 1.9 phr mercaptobenzothiazolyl disulfide (80%; containing 20% ​​by weight of binder and dispersant). In Comparative Example V1, zinc oxide had already been added in step 1.

[0336] First, the cooled composite sheet was cut into strips and the vulcanizing chemicals were weighed. After starting the rotor (50 rpm) at a mixing chamber temperature of 40°C, the sheet was fed into the mixing chamber, the filling device of the mixing chamber was pneumatically locked, and mixing was performed until the total mixing time was 2 minutes. Subsequently, the filling device of the mixing chamber was opened, the vulcanizing chemicals were added, the filling device of the mixing chamber was pneumatically locked, and mixing was performed until the total mixing time was 5 minutes. The injection temperature was controlled by adjusting the speed. Injection occurred after a total mixing time of 5 minutes and the temperature of the composite was measured.

[0337] After the mixing process, the compound is removed from the mixer and cooled and homogenized on a laboratory mill with a medium roll gap width. To this end, the mixture is first passed through the roll gap once, the resulting composite sheet is rolled into a "doll" and dropped from above through the roll gap six times. The sheet is then cooled on a cooling table until the sheet reaches room temperature.

[0338] This gives a vulcanizable composition V1 g and V2 g and B1 g , where "g" stands for "uncured compound" and the remaining names correspond to Examples V1, V2 and B1.

[0339] Preparation of vulcanized rubber compositions

[0340] The vulcanizable rubber composition V1 g and V2 g and B1 g , by vulcanizing at 160°C in a vulcanizer, a fully vulcanized test sample V1 was obtained v and V2 v and B1 v , which corresponds to the vulcanizable unvulcanized compound V1 g and V2 g and B1g . By continuously reducing the nip width of the laboratory roller, the composite sheet is rolled to a thickness of 3mm without wrinkles. Then cut a square of 250x 250mm from the sheet with scissors and transfer it to a press (Gibitre Instruments S.RL vulcanizing press, built-in mold for 2mm thick test plates). The curing time to be set is obtained by adding one minute per millimeter of sheet thickness (i.e., adding two minutes when using a 2mm frame) to the t90 time determined in the rheometer test. After the pressing time ends, remove the vulcanized rubber pad immediately. The pad is placed on a cooling table to cool. After cooling, carefully cut off the protruding edges with scissors.

[0341] Other rubber compositions containing filler F1B

[0342] The vulcanizable rubber compositions listed in Table 3 were prepared in the same manner as described above. Compared to Table 2, Table 3 specifies the rubber compositions including the ingredients added in the second stage and their amounts (ie, as "unvulcanized compounds").

[0343] Table 3

[0344]

[0345] Example V3 g 、V4 g and B2 g Corresponding to Example V1 g 、V2 g and B1 g (ie the "uncured compounds" of Examples V1, V2 and B1), except that filler F1B was used instead of filler F1A. F1B had a slightly lower multi-point BET surface area and a slightly lower STSA surface area (see Table 1).

[0346] In Example V5 g 、V6 g and B3 g In the above examples, part of filler F1B was replaced by carbon black with different BET or STSA surface. The ratio of FB1 to carbon black was 40:10.

[0347] In Example V7 g and B4 g In the experiment, part of filler F1B was replaced by carbon black with different BET or STSA surface. The ratio of FB1 to carbon black was 40:15. The content of process oil was also slightly increased.

[0348] Other rubber compositions containing filler F1C

[0349] The vulcanizable rubber compositions listed in Table 4 were prepared in the same manner as described above. The representation in Table 4 is similar to that in Table 3.

[0350] Table 4

[0351]

[0352] The above examples in Table 4 show that blends of brominated butyl rubber (X Butyl BB 2030) or chlorobutyl rubber (X-Butyl CB 1240) with natural rubber (SMR CV) can also be produced using filler F1C. Due to the advantages of using F1 filler in brominated butyl rubber in reducing gas permeability, as described in the results section, part of the brominated butyl rubber can be replaced by natural rubber, which has a slightly higher gas permeability but has the advantage of being a bio-sourced product while maintaining a sufficiently good gas permeability. By increasing the amount of F1c, the advantages associated with filler F1 can also be improved. The crosslinking chemistry has been adjusted so that it is suitable for blending with natural rubber.

[0353] Test results

[0354] In Table 5, the vulcanizable rubber composition V1 is reported. g 、V2 g and B1 g (Using filler F1A) and V3 g 、V4 g and B2 g Test results of reaction kinetics / vulcanization kinetics (using filler F1B).

[0355] Table 5

[0356] Variables measured unit <![CDATA[V1 g ]]> <![CDATA[V2 g ]]> <![CDATA[B1 g ]]> <![CDATA[V3 g ]]> <![CDATA[V4 g ]]> <![CDATA[B2 g ]]> <![CDATA[M L ]]> dN 1.28 1.65 1.93 1.50 1.85 1.92 <![CDATA[M H ]]> dN 5.68 5.28 6.02 6.24 6.48 6.86 <![CDATA[Δ(M H -M L )]]> dN 4.40 3.63 4.09 4.74 4.63 4.94 <![CDATA[T 10 ]]> min 2.75 2.29 2.23 3.05 3.75 3.49 <![CDATA[T 50 ]]> min 7.50 10.71 10.68 8.63 20.41 17.43 <![CDATA[T 90 ]]> min 15.36 24.92 25.03 17.59 57.19 47.19

[0357] As shown in Table 5, carbon black N660 V1 g and V3 g The data for the reference mixture were within the tolerable range. However, V4 g and B2 g The technical literature on BIIR crosslinking with ZnO states that water acts as a strong retarder. The HTT lignin used reaches equilibrium at a water absorption of about 2.5%. This is significantly higher than the water absorbed by carbon black N660. During the vulcanization, the influence of the reaction kinetics was taken into account by vulcanizing test specimens of each mixture for the time measured at T90.

[0358] Table 6 shows the comparative example V1 v 、V2 v and Inventive Example B1 v The measured values ​​are obtained from the vulcanized test specimens.

[0359] Table 6

[0360] Variables measured unit <![CDATA[V1 v ]]> <![CDATA[V2 v ]]> <![CDATA[B1 v ]]> Shore A Hardness - 52 46 50 density <![CDATA[g / cm 3 ]]> 1.120 1.019 1.027 Gas permeability <![CDATA[10 -17 m 2 / Not]]> 3.88 3.15 2.91 Compression set at 70℃ for 22 hours % 42.7 36.8 36.6 Modulus 100 MPa 1.0 0.7 0.9 Modulus 200 MPa 2.1 1.3 1.8 Modulus 300 MPa 3.5 2.4 3.3 Modulus 300 / Modulus 100 - 3.5 3.4 3.7 tensile strength MPa 10.9 8.1 8.4 Elongation at break % 727 665 569

[0361] As shown in Table 6, when using HTT lignin, the gas permeability is improved even with the same volumetric dosage (considering the low density of the filler). v Likewise, a slight increase in the volume filling level will increase the gas permeability

[0362] The improvement is about 25%. The reinforcement index M300 / M100 is also improved with B1v. The values ​​of tensile strength and elongation at break are within the acceptable range for the use of this composite in inner liners.

[0363] Table 7 shows the comparative example V3 v 、V4 v and Example B2 according to the present invention v The measured values ​​are obtained from the vulcanized test specimens.

[0364] Table 7

[0365]

[0366] As shown in Table 7, when HTT lignin was used, composite V4 v and B2 v The reinforcing properties of up to 300% elongation are higher than the carbon black reference, which is also clearly reflected in the reinforcement index M300 / M100. Equally important, the average molecular network arc length Mc, determined by toluene swelling using the Flory-Huggins constant (0.35), is slightly lower. Despite the higher network density and higher modulus (up to 300% deformation), B2 v In particular, the inhibition of crack propagation is shown to be improved. This is all the more pronounced since the composite with HTT lignin is subject to greater forces at the crack site.

[0367] Table 8

[0368] Variables measured unit <![CDATA[V5 g ]]> <![CDATA[V6 g ]]> <![CDATA[B3 g ]]> <![CDATA[V7 g ]]> <![CDATA[B4 g ]]> <![CDATA[M L ]]> dN 1.87 1.79 1.73 1.61 1.68 <![CDATA[M H ]]> dN 6.57 5.95 6.58 5.71 6.34 <![CDATA[Δ(M H -M L )]]> dN 4.70 4.16 4.85 4.10 4.66 <![CDATA[T 10 ]]> minute 3.86 3.68 3.27 3.46 3.40 <![CDATA[T 50 ]]> minute 18.40 18.25 15.76 15.00 16.55 <![CDATA[T 90 ]]> minute 47.83 47.74 40.35 35.20 41.83

[0369] As shown in Table 8, when measuring the cross-linking kinetics, replacing N772 with N326 showed higher Δ torque (M H- M L ), which indicates a higher enhancement effect. On the other hand, M L It was barely affected at these doses, indicating good processing properties of N326.

[0370] Table 9

[0371]

[0372] As shown in Table 9, replacing carbon black N772 with carbon black N326 shows an increase in stress values ​​(modulus 100-300), tensile strength, elongation at break and hardness. However, it is particularly surprising that despite these higher stress values, an improvement in crack growth is achieved.

Claims

1. A rubber composition, comprising: Rubber component, the rubber component comprising at least one halogenated butyl rubber selected from the group consisting of brominated butyl rubber and chlorinated butyl rubber, and Filler ingredient, the filler ingredient Contains one or more fillers F1, the filler F1 Has 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon; The carbon content is in the range of 60% to 85% by weight relative to the ash-free and water-free filler; having acidic hydroxyl groups on its surface; wherein The weighted arithmetic mean of the STSA surface area of ​​the filler F1 is 40 m 2 / g to 80m 2 / g range; The volume-based median particle size distribution D of the filler F1 is v (50) In the range of 0.5 μm to 5 μm, the volume-based D v (97) values ​​range from 3 μm to 23 μm; and i. the filler component contains more than 45 phr of filler F1; or ii. The filler component comprises more than 25 phr of filler F1 and further comprises one or more industrial carbon blacks F2, wherein the weighted arithmetic mean of the STSA surface area of ​​the industrial carbon blacks F2 is between 55 m 2 / g to 95m 2 / g range; The amount of the halogenated butyl rubber in the rubber composition is 60 phr to 100 phr.

2. The rubber composition according to claim 1, characterized in that The STSA surface area of ​​each filler F1 is 40m 2 / g to 80m 2 / g, and the STSA surface area of ​​each industrial carbon black F2 is 55 m 2 / g to 95m 2 / g range.

3. The rubber composition according to any one of claims 1 or 2, characterized in that The rubber composition comprises one or more other components selected from the group consisting of: i. Rubber other than halogenated butyl rubber, ii. a filler F3 different from the fillers F1 and F2, iii. Softener, iv. Adhesion enhancing resins, and v. Additives that promote vulcanization.

4. The rubber composition according to claim 3, characterized in that i. the rubber other than halogenated butyl rubber is selected from the group consisting of natural rubber, butyl rubber and styrene-butadiene rubber, and / or ii. the filler F3 different from the filler F1 and the filler F2 is selected from the group consisting of carbon black and layered silicate, and / or iii. the softener is selected from the group consisting of esters of aliphatic dicarboxylic acids, paraffin oils and naphthenic oils, and / or iv. the adhesion enhancing resin is selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins and phenol acetylene resins; and / or v. The vulcanization-promoting additive is selected from the group consisting of saturated fatty acids having 12 to 24 carbon atoms and thiazoles.

5. The rubber composition according to any one of claims 3 or 4, characterized in that i. the content of the rubber other than the halogenated butyl rubber in the rubber composition is 0 phr to 40 phr, and / or ii. the content of the filler F3 different from the filler F1 and the filler F2 in the rubber composition is 0 phr to 40 phr, and / or iii. the content of the softener in the rubber composition is 0 phr to 20 phr, and / or iv. The content of the adhesion enhancing resin in the rubber composition is 0 phr to 15 phr; and / or v. The content of the vulcanization-accelerating additive in the rubber composition is 0 phr to 5 phr.

6. The rubber composition according to any one or more of the preceding claims, characterized in that The filler F1 is a lignin-based filler, preferably a hydrothermally treated lignin.

7. The rubber composition according to one or more of the preceding claims, characterized in that The filler or fillers F1 are present in an amount ranging from 50% to 100% by weight, based on the total amount of fillers F1 and F2, and / or the total amount of fillers F1 and F2 is at least 46 phr.

8. The rubber composition according to any one of the preceding claims, characterized in that According to Sipponen, the amount of available acidic hydroxyl groups on the surface of the filler F1 is in the range of 0.05 mmol / g to 5 mmol / g.

9. A vulcanizable rubber composition, comprising: A rubber composition as claimed in any one or more of claims 1 to 8 and a vulcanization system comprising zinc oxide and / or sulfur.

10. The vulcanizable rubber composition according to claim 9, characterized in that The vulcanization system is selected from the group consisting of the following vulcanization systems comprising zinc oxide and: a. at least one saturated fatty acid having 12 to 24 carbon atoms; b. at least one thiuram and / or dithiocarbamate / salt, preferably free of sulfur; c. at least one alkylphenol disulfide; d. at least a polyhydroxymethylphenol resin or a halogenated polyhydroxymethylphenol resin, preferably free of sulfur and free of sulfur-containing compounds; e. sulfur and at least one thiazole and / or sulfenamide; f. Sulfur, at least one thiazole and / or sulfenamide and at least one saturated fatty acid having 12 to 24 carbon atoms.

11. A kit of parts comprising, in spatially separated form, a rubber composition (A) as claimed in any one or more of claims 1 to 8 and a vulcanization system (B) as defined in claim 9 or 10.

12. A method for preparing a rubber composition as defined in any one or more of claims 1 to 8, characterized in that A rubber component is provided and a filler component and optionally a softener, an adhesion enhancing resin and an additive to accelerate vulcanization are incorporated therein.

13. A method for preparing the vulcanizable rubber composition according to any one of claims 9 or 10, characterized in that: In a first stage, the rubber composition is prepared according to the process according to claim 12, and then in a second stage, the mixing of the components of the vulcanization system is carried out.

14. A method for further processing the inventive vulcanizable rubber composition defined in claims 9 and 10, characterized in that It is formed into a web by calendaring, extrusion or roll head process.

15. The method according to claim 14, characterized in that The thickness of the mesh is in the range of 0.3 mm to 5 mm.

16. A method for manufacturing a pneumatic tire, said method comprising the method according to claim 14 or 15, followed by a step of cutting said web to the size of a pneumatic tire innerliner, and comprising a subsequent step of vulcanizing the innerliner thus obtained together with a pneumatic tire carcass.

17. Use of one or more fillers F1 in a rubber composition for innerlining, the fillers F1 optionally mixed with one or more industrial carbon blacks F2, the fillers F1 and the industrial carbon blacks F2 being as defined in any one of claims 1, 6, 7 or 8, wherein the fillers F1 and the industrial carbon blacks F2 are used in a total amount of at least 46 phr.

18. A vulcanized rubber composition obtainable by vulcanizing the vulcanizable rubber composition according to any one of claims 9 or 10.

19. The vulcanized rubber composition according to claim 18, wherein The vulcanized rubber composition has: (a) a Shore A hardness in the range of 35 to 65, and / or (b) a modulus 300 of 2.8 MPa to 8 MPa; and / or (c) Density: 1.000 g / cm 3 Up to 1.120g / cm 3 ; and / or (d) Gas permeability is less than 3.8×10 -17 m 2 / Pas.

20. The vulcanized rubber composition according to claim 18 or 19, characterized in that The vulcanized rubber composition is an inner liner of a pneumatic tire.